(untitled) (Nepalese Veterinary Journal, 2018)
The present study was undertaken to determine the effect of age and frequency of collection on quality parameters of Jersey bull semen at National Livestock Breeding Center (NLBC), Pokhara, Kaski district. Nine Jersey bulls were selected randomly from NLBC. To obtain the effect of age, six bulls of three different age interval (3- 4, 5-7 and 8-9 years) were selected randomly. Remaining three bulls were used to determine the effect of frequency of collection on semen quality. Studies were conducted for three months (Nov/Dec to Dec/Jan 2017). Semen quality was analyzed using CASA system and SMILE software. ANOVA and paired t- tests were applied to find out level of significance. All the statistical analyses were done using SPSS 17.0. Sperm concentration (0.551 ±0.004 to 1.084 ± 0.014x109), post- thaw motility (42.44±0.11 to 51.72±0.03 %), live sperm (45.62 ± 0.13 to 51.23±0.15 %), and abnormal sperm (11.57±0.12 to 19.59±0.24%) were significantly affected by the age of the bulls. Semen quality was found superior in the bulls belonging to 5-7 years of age intervals. On the other hand, volume (3.98±0.09 to 6.72±0.06 ml), initial motility (72.68±0.02 to 78.64±0.15 %) and pre-filling motility (71.34±0.17 to 77.62±0.02 %) did not differ significantly among different age intervals. Significantly, higher value for semen volume (3.98±0.12 to 6.02±0.14 ml), sperm concentration (0.572±0.119 to 1.095±0.015) and post- thaw motility (40.34±0.21 to 48.54±0.06% was obtained on second collection. However, initial motility (70.58±0.06 to 75.64±0.13 %), prefilling motility (68.11±0.12 to 71.62±0.02 %), live sperm (53.27±0.54 to 56.17±0.02 %) and abnormal sperm (12.31±0.12 to 14.3±0.47 %) did not differ significantly between the frequencies of collection. Different quality parameters of semen like volume, concentration, initial motility, pre-filling motility, post thaw motility, live and normal spermatozoa percentage were higher in 5-7 years old bulls and in second collection of semen.